Interaction of reproductive tract infections with estrogen exposure on breast cancer risk and prognosis - YunQian Li; XingLi Gan; ZhuoZhi Liang; HengMing Ye; Ying Lin; Qiang Liu; XiaoMing Xie; LuYing Tang; ZeFang Ren (BMC, 2023)
Abstract Background Reproductive tract infections influenced a series of inflammatory processes which involved in the development of breast cancer, while the processes were largely affected by estrogen. The present study aimed to explore the associations of breast cancer risk and prognosis with reproductive tract infections and the modification effects of estrogen exposure. Methods We collected history of reproductive tract infections, menstruation and reproduction from 1003 cases and 1107 controls and a cohort of 4264 breast cancer patients during 2008-2018 in Guangzhou, China. We used logistic regression model to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for risk; Cox model was applied to estimate the hazard ratios (HRs) and 95% CIs for progression-free survival (PFS) and overall survival (OS). Results It was found that previous reproductive tract infections were negatively associated with breast cancer risk (OR = 0.80, 95%CI, 0.65-0.98), particularly for patients with more menstrual cycles (OR = 0.74, 95%CI, 0.57-0.96). Patients with previous reproductive tract infections experienced better OS (HR = 0.61; 95% CI, 0.40-0.94) and PFS (HR = 0.84; 95% CI, 0.65-1.09). This protective effect on PFS was only found in patients with more menstrual cycles (HR = 0.52, 95% CI:0.34-0.79, P interaction = 0.015). Conclusions The findings suggested that reproductive tract infections may be protective for the initiation and development of breast cancer, particularly for women with a longer interval of lifetime estrogen exposure.